The Impact Mechanism of Negative Academic Emotions on Academic Procrastination: The Mediating and Moderating Roles of Self-Efficacy and Goal Orientation - Bowen Chen; Hongfeng Zhang; Sigan Li (MDPI AG, 2024)
Academic procrastination is a widespread phenomenon among college students, significantly affecting their academic performance and mental health. Although previous studies have suggested a relationship between negative academic emotions and academic procrastination, the underlying mechanisms of this relationship remain insufficiently explored. Based on theoretical analysis and a review of the literature, this study utilizes structural equation modeling to examine the effects of negative academic emotions, self-efficacy, and goal orientation on academic procrastination. The results indicate a significant positive correlation between negative emotions and academic procrastination. Furthermore, self-efficacy fully mediates the relationship between negative academic emotions and academic procrastination, while goal orientation plays a moderating role in this relationship. This study reveals the intricate relationships between negative academic emotions and academic procrastination among Chinese college students, emphasizing the importance of enhancing self-efficacy and goal orientation to prevent procrastination. It provides theoretical and empirical support for improving learning efficiency and academic achievement, as well as for designing interventions to address academic procrastination.